Relation of Some Known Functions in terms of Generalized Meijer G-Functions - Syed Ali Haider Shah; Shahid Mubeen; Gauhar Rahman; Jihad Younis (Journal of Mathematics)
The aim of this paper is to prove some identities in the form of generalized Meijer G-function. We prove the relation of some known functions such as exponential functions, sine and cosine functions, product of exponential and trigonometric functions, product of exponential and hyperbolic functions, binomial expansion, logarithmic function, and sine integral, with the generalized Meijer G-function. We also prove the product of modified Bessel function of first and second kind in the form of generalized Meijer G-function and solve an integral involving the product of modified Bessel functions.